2022
DOI: 10.37341/interest.v0i0.346
|View full text |Cite
|
Sign up to set email alerts
|

Spiritual Deep Breathing Exercise Is Effective In Reducing Anxiety And Stabilizing Oxygen Saturation In COVID-19 Patients

Abstract: Background: Problems that arise in COVID-19 patients include, often experiencing deep anxiety characterized by fear of pain, fear of death, fear of losing personal independence, fear of losing role functions that can cause physiological changes, namely a decrease in Oxygen Saturation (SaO2). Methods: The design of this study was a quasi-experimental approach with a Pretest-Posttest Control Group Design approach. The population of all COVID-19 patients at the Surabaya A. Yani Islamic Hospital is 187 peop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
0
0
Order By: Relevance
“…Additionally, Muthoharoh et al 51 investigated the impact of diaphragmatic deep breathing exercise on COVID-19 patients. The results revealed that there was a significant enhancement in oxygen saturation evaluated by pulse oximeter.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Muthoharoh et al 51 investigated the impact of diaphragmatic deep breathing exercise on COVID-19 patients. The results revealed that there was a significant enhancement in oxygen saturation evaluated by pulse oximeter.…”
Section: Discussionmentioning
confidence: 99%